Biofortification as a food-based strategy to improve nutrition in high-income countries: A scoping review - Gulyas, Boglarka Z.; Mogeni, Brenda; Jackson, Peter; Walton, Jenny; Caton, Samantha J. (Informa UK Limited, 2025)
Biofortification (increasing the micronutrient content of food before harvest) has been successfully used to nutritionally improve staple foods in low- and middle-income countries. This approach could also help address micronutrient shortfalls in at-risk populations in high-income countries (HICs), however, the potential of biofortification interventions in this context is not well understood. The aim of this scoping review is to assess the nature and extent of available research evidence on biofortified foods in relation to human consumption in HICs. Literature searches were conducted in MEDLINE, WoS, ProQuest, CINAHL, AGRIS and Epistemonikos. Forty-six peer-reviewed articles were included. Most research was conducted in the USA (n = 15) and Italy (n = 11), on cereal crops (n = 14) and vegetables (n = 11), and on selenium (n = 12) and provitamin A (n = 11). Seven research domains were identified in the literature: bioavailability (n = 17); nutrient stability (n = 11); opinions and attitudes (n = 9); functionality (n = 9); sensory properties (n = 2); safety (n = 1); and modeling (n = 1). Evidence from HICs in each domain is limited. There is a need for more research particularly in areas sensitive to the cultural and socio-economic context.